Construction and finite element simulation of a square laser loading model that can replace circular spot superposition in laser peening forming - Xu PEI; Boyong SU; Liang WANG (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2025)
In order to explore an efficient, accurate, and convenient finite element simulation method for laser peening forming, a square laser loading model was constructed by studying the loading feature unit of the circular spot superposition model, which can replace the circular spots overlay laser peening forming. and Finite element simulation was conducted on 7075 aluminum alloy flat plate model. In order to verify the rationality and effectiveness of the square finite element loading model and its finite element simulation method, a finite element model base on 7075 aluminum alloy flat plate was used as the object for simulation. The corresponding experiment of 7075 aluminum alloy flat plate laser peening forming was conducted, and the experimental results were compared with the finite element analysis results. The results indicate that the finite element simulation results comply with experimental laws in terms of stress and forming. After laser peening forming, both finite element simulation and experimental results show that high amplitude residual compressive stress is generated on the surface of the metal plate. Compared with the experimental results, the magnitude and overall trend of residual stress at different positions are consistent. And the free end offset of the upper surface of the formed metal plate obtained from finite element simulation and experiments, as well as the arch span and height of the surface contour curve in the forming area of the metal plate, are similar. This indicates that the constructed square laser loading model and its finite element simulation method are reasonable, effective and in accordance with experimental laws. Finally, the reasons for sheet metal forming under laser peening were attributed to the gradient plastic extension effect driven by the surface material of the substrate under the effect of laser shot peening.